Protagonismo juvenil nas aulas de educação física: análise da construção de uma sequência didática com discentes do ensino fundamental - Castro, Rosemeire Brasilio (2024)
This study emerged from a concern within my teaching practice regarding the increasing number of students disengaging from Physical Education classes during the later years of Elementary School. The factors discouraging student commitment are often complex, particularly those related to risk factors stemming from various sociocultural contexts, which frequently lead to the adoption of detrimental lifestyles. This, in turn, impacts adolescent health and directly influences their participation in Physical Education classes. To address this issue, this study aimed to describe the collaborative development of a didactic sequence focusing on youth protagonism with students from a 9th-grade class, and to analyze its implementation, aiming to understand the impacts and contributions of this approach. A qualitative research methodology, employing Pedagogical Intervention, was utilized with 20 9th-grade students from a municipal school in São Paulo, using Field Notes as the primary data collection tool. Data analysis involved the development of Coding Categories, resulting in the following categories: A) Challenges in Teaching Practice: Context and School Culture – Explores the influence of local context, school culture, educational structures, and institutional dynamics on teaching practice; B) Protagonism and Protagonists – Analyzes the individual and collective protagonism of students and the teacher-researcher during the didactic sequence development; C) Pedagogical Approaches and the Development of Critical Thinking in School Physical Education – Investigates the transition from traditional to active methodologies in School Physical Education, and its impact on students' critical consciousness; D) Playful Learning as Empowerment for Conscious Choices in Youth – Explores how playful learning, through games, enhances students' understanding of risks and life choices, and whether this approach positively influences the development of their values. Through the lens of youth protagonism, student participation in the educational process facilitated collective knowledge construction. Thus, the school environment serves as a platform for a significant portion of these young individuals to develop fundamental critical thinking skills. Consequently, this research, through dialogue with the students, contributed to the reflection on social issues. It is hoped that this study will inform future research on youth protagonism in School Physical Education.